Metal-Ligand Cooperativity to Assemble a Neutral and Terminal Niobium Phosphorus Triple Bond (Nb equivalent to P) - Senthil, Shuruthi; Kwon, Seongyeon; Fehn, Dominik; Im, Hoyoung; Gau, Michael R.; Carroll, Patrick J.; Baik, Mu-Hyun; Meyer, Karsten; Mindiola, Daniel J. (Angewandte Chemie International Edition, 2022)
Decarbonylation along with P-atom transfer from the phosphaethynolate anion, PCO-, to the Nb-IV complex [(PNP)NbCl2((NBuAr)-Bu-t)] (1) (PNP=N[2-(PPr2)-Pr-i-4-methylphenyl](2)(-); Ar=3,5-Me2C6H3) results in its coupling with one of the phosphine arms of the pincer ligand to produce a phosphanylidene phosphorane complex [(PNPP)NbCl((NBuAr)-Bu-t)] (2). Reduction of 2 with CoCp*(2) cleaves the P-P bond to form the first neutral and terminal phosphido complex of a group 5 transition metal, namely, [(PNP)Nb equivalent to P((NBuAr)-Bu-t)] (3). Theoretical studies have been used to understand both the coupling of the P-atom and the reductive cleavage of the P-P bond. Reaction of 3 with a two-electron oxidant such as ethylene sulfide results in a diamagnetic sulfido complex having a P-P coupled ligand, namely [(PNPP)Nb=S((NBuAr)-Bu-t)] (4).
CRIS-Team WoS Importer:2022-12-09